Chylomicronemia risk factors ranked by importance for the individual and community in 108 711 women and men. (4th December 2017) - Pedersen, S. B.; Varbo, A.; Langsted, A.; Nordestgaard, B. G.
Abstract: Background: Hypertriglyceridemia prevalence is increasing as more individuals become obese, and chylomicronemia risk factors for the individual and community have not been described previously. Objective: To describe chylomicronemia risk factors in the general population for individuals and community. Methods: A total of 108 711 individuals from the Copenhagen General Population Study were grouped as unlikely chylomicronemia (nonfasting triglycerides <2 mmol L −1 (177 mg dL −1 )), possible chylomicronemia (2–4.99 mmol L −1 (177–442 mg dL −1 )), probable chylomicronemia (5–9.99 mmol L −1 (443–885 mg dL −1 )) and definite chylomicronemia (≥10 mmol L −1 (≥ 886 mg dL −1 )). Relative risk (RR) from Poisson regression ranked dichotomized chylomicronemia risk factors for individuals, and population attributable fractions (PAF) for the community: type 2 diabetes, alcohol intake, obesity, fat intake, hypothyroidism, kidney function, education, sedentary lifestyle, menopause and hormone replacement (women). Results: For women and men, chylomicronemia was unlikely in 81% and 64%, possible in 18% and 33%, probable in 1% and 3% and definite in 0.03% and 0.14%, respectively. For the individual, the three top‐ranked risk factors for probable/definite versus unlikely chylomicronemia in women were type 2 diabetes (RR: 4.21; 95% confidence interval: 3.30–5.36), menopause (RR: 3.74; 2.62–5.36) and obesity (RR: 3.44; 2.81–4.21). Corresponding top‐ranked risk factors in men were obesity (RR: 3.86; 3.46–4.30), type 2 diabetes (RR: 1.88; 1.61–2.19) and reduced kidney function (RR: 1.86; 1.48–2.34). For the community, top‐ranked risk factors in women were menopause (PAF: 63%), obesity (PAF: 29%) and type 2 diabetes (PAF: 15%). Corresponding top‐ranked risk factors in men were obesity (PAF: 29%), type 2 diabetes (PAF: 6.4%) and sedentary lifestyle (PAF: 6.0%). Conclusions: Obesity and type 2 diabetes were the most important modifiable chylomicronemia risk factors in women and men, both for the individual and community. This could influence chylomicronemia prevention and help design randomized trials aimed at reducing triglycerides. Abstract : Click here to view the Editorial Comment by A. J. Berberich & R. A. Hegele